(untitled) (Journal of Engineering, 2013)
Rhythm is considered one of the creative concepts in the recent architectural thought; it has emerged clearly as a mean of creating the highest levels of creativity in architecture, especially in contemporary architectural movements. The importance of rhythm has emerged, especially, when the architecture , its beginnings concentrated on the principle of the links with poetic structures. Many architectural studies deal with concept of rhythm in architecture with different ways various according to the trend of each study, this show the importance of studying the concept of rhythm in the architectural field in general. This study try to focus on the utilization of rhythm as creative system in architecture of heritage and contemporary house because its important in the generation of new architectural models. The paper discusses the importance of this concept and its utilization in the designs, in order to explore the particular problem which has been represented as (The absence of a specific imagination of methods and strategies for achieving rhythm).Thus the objectives of the paper has been formed by building theoretical framework consisting of five main items of detailed theoretical field which specifies rhythm as a concept ,firstly, then the application of the important heritage and contemporary houses in Mosul Architecture as a model, concluding utilization of rhythm as creative system in Heritage and Contemporary Houses in Mosul Architecture, finally, after discussing the results to submit the conclusions in the end. The conclusion is That suitable rhythm creativity in Mosul architecture is by unit and immerge the Mosul cultural elements as new tool in steps of design process of Heritage and Contemporary Houses in Mosul.